Development Of Community Based Ecotourism In Bahoi Village, West Likupang District, North Minahasa Regency - Asari, Ayu; Toloh, Boyke H.; Sangari, Joudy R. R. (Sam Ratulangi University, 2018)
In the spatial development of North Sulawesi Province, Bahoi Village is one of the coral reef conservation development areas developed into community based ecotourism village. One area that has the potential is Bahoi Village District West Likupang North Minahasa District with the concept of marine community-based ecotourism. This potential is supported by Regional Regulation No. 1 of 2014 in North Sulawesi Province Spatial Planning. This study aims to determine the status of ecotourism development in Bahoi Village and evaluate the principles and concepts of ecotourism using a qualitative descriptive method. In this research, the data were taken by conducting literature study, verification, field survey, and an interview. Interviews were conducted using questionnaires as many as 18 questions/statements containing topics on the management of ecotourism in Bahoi Village, ecotourism concepts, and principles. Questions are presented and analyzed using R and SPSS programs. R is an integrated software unit with several facilities for manipulation, calculation, and reliable graphics performance. SPSS is an application that has a high enough statistical analysis capability and data management systems in the graphical environment by using descriptive menus in simple dialog boxes and easy to understand how to operate. Based on the results of the analysis, there are several problems concerning the management of ecotourism that still overlap, ecotourism principles that have not been reached, especially on economic principles, and the lack of community empowerment. Through this research it can be concluded that ecotourism of Bahoi Village has not given full impact, ecotourism management which is not good can, in turn, forget the economic interest of the local community, and there is urgent need to make Standard Operational Procedure (SOP) of ecotourism for community-based ecotourism management. Furthermore, the concept and principles of ecotourism that has not been applied thoroughly then need to be reviewed for better future.Keywords: development, marine ecotourism, ecotourism management, Bahoi villageABSTRAKDalam pengembangan tata ruang Wilayah Provinsi Sulawesi Utara. Desa Bahoi merupakan salah satu kawasan pengembangan koservasi terumbu karang yang dikembangkan menjadi Desa Ekowisata Berbasis Masyarakat.Salah satu wilayah yang memiliki potensi tersebut yaitu Desa Bahoi Kecamatan Likupang Barat Kabupaten Minahasa Utara dengan konsep ekowisata bahari berbasis masyarakat. Potensi ini didukung dengan Peraturan Daerah Nomor 1 Tahun 2014 tentang Rencana Tata Ruang Wilayah Provinsi Sulawesi Utara yaitu Desa Bahoi merupakan salah satu kawasan pengembangan konservasi terumbu karang.Penelitian ini bertujuan untuk mengetahui status pengembangan ekowisata yang ada di Desa Bahoi dan mengevaluasi prinsip-prinsip dan konsep ekowisata menggunakan metode deskriptif kualitatif. Dalam penelitian ini data di ambil dengan studi literature, verifikasi, survei lapangan dan wawancara. Wawancara dilakukan dengan menggunakan kuesioner sebanyak 18 Pertanyaan/pernyataan yang berisisi tentang pengelolaan ekowisata di Desa Bahoi, konsep dan prinsip-prinsip ekowisata. Pertanyaan disajikan dan di analisis menggunakan program R dan SPSS. R adalah suatu kesatuan software yang terintegrasi dengan beberapa fasilitas untuk manipulasi, perhitungan dan penampilan grafik yang handal. SPSS adalah sebuah program aplikasi yang memiliki kemampuan analisis statistik cukup tinggi serta sistem manajemen data pada lingkungan grafis dengan menggunakan menu-menu deskriptif dan kotak-kotak dialog yang sederhana sehingga mudah untuk dipahami cara pengoperasiannya. Berdasarkan hasil analisis yang dilakukan terdapat beberapa masalah mengenai pengelolaan ekowisata yang masih tumpang tindih, peinsip-prinsip ekowisata yang belum tercapai terutama pada prinsip ekonomi, kurangnya pemberdayaan masyarakat .Dari penelitian ini dapat ditarik kesimpulan ekowisata Desa Bahoi belum memeberi dampak secara menyeluruh, pengolaan ekowisata yang kurang baik dapat melupakan kepentingan ekonomi masyarakat lokal untuk itu perlu di buat Standar Operasional Prosedur ekowisata yang mengatur manajemen ekowisata,. Kosep dan prinsip-prinsip ekowisata yang belum diterapkan secara menyeluruhÂ maka perlu di kaji kembali.Kata Kunci: Kajian pengembangan, ekowisata bahari, pengelolaan Ekowisata, Desa BahoiÂ